Development of a SOFC Power Generator for the Indian Market1. Issue 4 (27th April 2017) - Pfeifer, T.; Chakradeo, A.; Ahire, N.; Baade, J.; Barthel, M.; Dosch, C.; Näke, R.; Hartmann, M.
Abstract: Contracted by the company h2e Power Systems Pvt. Ltd. based in Pune, India, Fraunhofer IKTS has developed a 1 kW(el) solid oxide fuel cell (SOFC) power generator during a three year system engineering and technology transfer project. The fuel cell system is based on the CFY stack technology by Plansee SE and IKTS, which incorporates state‐of‐the‐art ESC with Scandia‐doped Zirconia electrolytes. For the SOFC power generator, a chromium based interconnects (CFY) stack was integrated with a pre‐reformer, a tail‐gas oxidizer and heat exchangers into a HotBox‐module following a novel concept for least‐space‐demanding reactor integration and flow distribution. The applied system concept aimed at a very compact and robust, yet highly efficient power generator with optional heat extraction. Two major design decisions have been introduced in the process layout, i.e., a rated fuel utilization in the stack of 85% as well as a POX‐air pre‐heater for reducing the reformer air flow to lowest possible values. This approach lead to a waterless SOFC system with a net electrical efficiency above 40%. Two proof‐of‐concept (PoC) prototype systems were commissioned and tested for system concept validation. Based on the operating experience, three improved prototype units were built at IKTS and shipped to India for initial demonstration projects and field trials at the customer's site. At the same time, the technology transfer to the customer was initiated, in order to enable for a local manufacturing and deployment of SOFC systems in India. This paper outlines the system development approach and major technical achievements demonstrated on PoC prototype level.